Pengaruh Kualitas Produk, Brand Image, dan Promosi Terhadap Keputusan Pembelian Pada Plafon PVC Merek Shunda di Batam - Wiewin Wiranata; Mauli Siagian (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The rapid development of the property sector in Batam City has driven the increasing public demand for superior quality building materials. However, intense competition requires companies to pay attention to marketing factors that can influence consumer purchasing decisions. This study aims to analyze the influence of product quality, brand image, and promotion on purchasing decisions for Shunda brand PVC ceilings in Batam City. The research method used is a descriptive quantitative approach with a population of consumers who have purchased and used Shunda brand PVC ceilings. The sampling technique used purposive sampling with a total of 204 respondents. Data collection was carried out through questionnaires, then analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of the multiple linear regression analysis show that product quality influences purchasing decisions with a contribution of 20.2%, brand image influences with a contribution of 35.4%, and promotion contributes 21.8% to purchasing decisions. The coefficient of determination (R2) analysis reveals that product quality, brand image, and promotion are able to explain 79.8% of the variation in purchasing decisions for Shunda brand PVC ceilings in Batam City. The results of the t-test and F-test found that product quality, brand image, and promotion, both partially and simultaneously, had a significant influence on purchasing decisions for Shunda brand PVC ceilings in Batam City.